Un Dante polacco. Saggio sulla ricezione della figura e dell’opera dantesca in Polonia, dal Quattrocento a Miłosz - Chiara, Taraborrelli (University of Warsaw Press, 2025)
The book is an introduction to the reception of Dante Alighieri’s Divine Comedy in Poland and its main trends, from the Renaissance to the end of the 20th century. The author strives to prove how deep and long-lasting the influence of Dante’s work was on many renowned Polish writers, poets, and thinkers, with a focus on the slow but steady process of assimilation through which Dante and his masterpiece have become part of Polish culture.